Healthcare-Associated Pneumonia: Don't Forget About Respiratory Viruses! - Torres-García, Margarita; Pérez Méndez, Brenda Berenice; Sánchez Huerta, José Luis; Villa Guillén, Mónica; Rementería Vazquez, Virydiana; Castro Diaz, Arturo Daniel; López Martinez, Briceida; Laris González, Almudena; Jiménez-Juárez, Rodolfo Norberto; de la Rosa-Zamboni, Daniela (Frontiers in Pediatrics, 2019)
Introduction. Healthcare-associated infections are an important cause of morbidity, mortality and are among the most adverse events common in healthcare, and among these the pneumonia is the most commonly reported. Our objective was to evaluate the incidence and clinical outcome of respiratory viruses in hospital-acquired pneumonia (HAP). Methods. This was a prospective cohort study, include patients 0-18 years of age who fulfilled CDC criteria for HAP, demographic and clinical data were obtained, and a nasopharyngeal swab specimen was taken for the detection of respiratory viruses. All included patients were followed up until discharge to collect data on the need for mechanical ventilation, ICU admission and mortality. All-cause 30-day mortality was also ascertained. Results. 4327 patients were followed for 42658 patient-days and 5150 ventilator-days. Eighty-eight patients (2.03%) met the CDC criteria for HAP, 63 patients were included, clinical and epidemiological characteristics showed no statistically significant differences between patients with VHAP and those with NVHAP. At least one respiratory virus was detected in 65% [95% CI (53-77)] of episodes of HAP, with a single viral pathogen observed in 53.9% and coinfection with 2 viruses in 11.1% of cases. The outcome in terms of intensive care unit admission, mechanical ventilation and the 30-day mortality did not show a significant difference between groups. Conclusions. There was no difference in mortality or the rest of the variables of clinical outcome. In 2 thirds of the patients a respiratory virus was identified, which emphasizes the importance of considering these pathogens in nosocomial infections, that their identification can influence the decrease in hospital costs and take account for infection control policies.